Respuesta :

Answer:

(8.5, - 2 )

Step-by-step explanation:

Given the 2 equations

6x + 4y = 43 → (1)

2x - 3y = 23 → (2)

Multiplying (2) by - 3 and adding to (1) will eliminate the term in x

- 6x + 9y = - 69 → (3)

Add (1) and (3) term by term to eliminate x, that is

13y = - 26 ( divide both sides by 13 )

y = - 2

Substitute y = - 2 in either of the 2 equations and solve for x

Substituting into (1)

6x + 4(- 2) = 43

6x - 8 = 43 ( add 8 to both sides )

6x = 51 ( divide both sides by 6 )

x = 8.5

Solution is (8.5, - 2 )